The Effects of Occupational Stress on Personnel’s Quality of Life and Desire to Continue Serving in Emergency Operation Center - Tahere Sharifi; Razieh Sepehrian; Mina Namdari (پژوهش‌های سلامت‌محور, 2016)
Introduction: The Emergency Operation Center (EOC) is a prehospital community-based health management system that its main capital are its employees. However, occupational stress in personnel have negative effect on their quality of life and can lead to leaving the occupation. The aim of this study was to evaluate occupational stress and its effect on quality of life and desire to continue serving in personnel of Emergency Operation Center in Kerman.